Replacement of Leishmania (Leishmania) infantum Populations in an Endemic Focus of Visceral Leishmaniasis in Brazil - Valdivia, Hugo O.; Roatt, Bruno M.; Baptista, Rodrigo de Paula; Ottino, Jennifer; Coqueiro-dos-Santos, Anderson; Sanders, Mandy J.; Reis, Alexandre B.; Cotton, James A.; Bartholomeu, Daniella C. (Frontiers in Cellular and Infection Microbiology, 2022)
Visceral leishmaniasis is an important global health problem with an estimated of 50,000 to 90,000 new cases per year. VL is the most serious form of leishmaniasis as it can be fatal in 95% of the cases if it remains untreated. VL is a particularly acute problem in Brazil which contributed with 97% of all cases reported in 2020 in the Americas. In this country, VL affects mainly the poorest people in both urban and rural areas and continues to have a high mortality rate estimated around 8.15%. Here, we performed a temporal parasite population study using whole genome sequence data from a set of 34 canine isolates sampled in 2008, 2012 and 2015 from a re-emergent focus in Southeastern Brazil. Our study found the presence of two distinct sexual subpopulations that corresponded to two isolation periods. These subpopulations diverged hundreds of years ago with no apparent gene flow between them suggesting a process of rapid replacement during a two-year period. Sequence comparisons and analysis of nucleotide diversity also showed evidence of balancing selection acting on transport-related genes and antigenic families. To our knowledge this is the first population genomic study showing a turn-over of parasite populations in an endemic region for leishmaniasis. The complexity and rapid adaptability of these parasites pose new challenges to control activities and demand more integrated approaches to understand this disease in New World foci.